Penggunaan Fitur Media Sosial Instagram Stories Sebagai Media Komunikasi - Martha, Zike (Jurnal Komunikasi Nusantara, 2021)
Instagram is one of the social media which is widely used by the public. They use the media not only to fill their free time, but also to reveal their previously hidden information. This study aims to find out how people reveal themselves through the Instagram story feature on social media of Instagram. This study uses descriptive qualitative research method with the theory of self-disclosure and the theory of Uses and Gratification as a theory in analyzing self-disclosure in Instagram story. Data collection techniques used were through interviews and documentation. The data were then analyzed using the stages of data reduction, data presentation, and drawing conclusion. The result showed that self-disclosure depends on the mood (mood) and tends to be due to the dyadic effect, and depends on the personality of an individual. The content of the message expressed in accordance with the needs and desires of an individual was also in accordance with the goals to be achieved based on the dimensions of the purpose of self-disclosure which are used as the unit of analysis in this study such as expression, self-cleaning, social control, and relationship development. to express feeling and self-development to gain self-awareness as social control, and to increase the intimacy of a relationship. Keywords: instagram story; self disclosure; uses and gratification